2005
DOI: 10.1080/02652040500100139
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cross-linked chitosan microspheres by spray drying: Effect of cross-linking agent on the properties of spray dried microspheres

Abstract: Chitosan microspheres cross-linked with three different cross-linking agents viz, tripolyphosphate (TPP), formaldehyde (FA) and gluteraldehyde (GA) have been prepared by spray drying technique. The influence of these cross-linking agents on the properties of spray dried chitosan microspheres was extensively investigated. The particle size and encapsulation efficiencies of thus prepared chitosan microspheres ranged mainly between 4.1-4.7 microm and 95.12-99.17%, respectively. Surface morphology, % erosion, % wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 27 publications
0
41
0
2
Order By: Relevance
“…Micropartículas com tamanho e morfologia similares foram reportadas por Desay e Park. 40 O processo de reticulação da quitosana é de grande importância, pois, além de promover a formação de uma rede polimérica na qual a enzima pode estar covalentemente ligada e/ou entrapeada, previne o intumescimento das micropartículas de quitosana em soluções aquosas, 41 favorecendo uma maior estabilidade da enzima imobilizada.…”
Section: Resultados E Discussão Morfologia Das Micropartículas De Quiunclassified
See 1 more Smart Citation
“…Micropartículas com tamanho e morfologia similares foram reportadas por Desay e Park. 40 O processo de reticulação da quitosana é de grande importância, pois, além de promover a formação de uma rede polimérica na qual a enzima pode estar covalentemente ligada e/ou entrapeada, previne o intumescimento das micropartículas de quitosana em soluções aquosas, 41 favorecendo uma maior estabilidade da enzima imobilizada.…”
Section: Resultados E Discussão Morfologia Das Micropartículas De Quiunclassified
“…39,40 Esse comportamento foi comprovado por alguns pesquisadores, 39,40 que realizaram estudos sistemáticos variando a concentração deste agente de reticulação e verificaram que micropartículas de quitosana reticuladas com TPP em excesso, obtidas por spray drying, apresentaram morfologia similar às apresentadas neste trabalho.…”
Section: Resultados E Discussão Morfologia Das Micropartículas De Quiunclassified
“…Concerning point "b", by increasing cross-linking agent there is an increase in the number of links between two cross-links that leads to a decrease in porosity (see table III), leading to a decrease in loading efficiency. Desai et al prepared chitosan microspheres by using three different cross-linkers and found a decrease in encapsulation when increasing cross-linker concentration from 1% to 2% (Desai, Park, 2005). Effect of pH on drug release was investigated by obtaining dissolution profiles at various pH such as 1.2, 5.5 and 7.5.…”
Section: Influence Of Different Parameters On Drug Loading and Releasmentioning
confidence: 99%
“…In addition, cross-linking of the chitosan can potentially influence the release pattern of the loaded drug. Glutaraldehyde is reported as the best cross-linking agent for various classes of drugs (Desai & Park, 2005). Hence, in the present study, glutaraldehyde was used as a cross-linking agent.…”
Section: Preparation and Characterization Of Microspheresmentioning
confidence: 99%